THE ROLE OF INVENTORY MANAGEMENT AND FORECASTING IN ORDER TO REDUCE DEADSTOCK AND IMPROVE INVENTORY MANAGEMENT AT PT THE PEAK CONNOISSEURS (The Indonesian Journal of Business Administration, 2019)
PT The Peak Connoisseurs is one of many alcoholic beverages distributor and retailer in Indonesia, it sells mostly wine and spirit. PT The Peak Connoisseurs are currently facing a problem, deadstock problem. This problem has been around since almost three years ago. Although the deadstock has been reduced, but it is still there. The purpose of this research is to reduce deadstock and improve inventory management in PT The Peak Connoisseurs.Current Reality Tree (CRT) is used to find the root cause of PT The Peak Connoisseur’s problem. There are several results from the root cause analysis using CRT, but the selected root causes are the lack of inventory management and forecasting.There are three methods that are used to solve this problem, ABC Classification, Forecasting, and Inventory Management. ABC Classification main purpose is to classified the important products from the unimportant. This research also use 6 methods of forecasting, there are Simple Moving Average, Weighted Moving Average, Trend Analysis, Single Exponential Smoothing, Double Exponential Smoothing, and Decomposition Method. Inventory Management is used to find the Economic Order Quantity (EOQ) and to optimize the cost.The result from the ABC Classification is Class A are the products with 80% contribution to the company total revenue, Class B are the products with 15% contribution to the company total revenue, Class C are the products with the 5% contribution to the company total revenue. There are 255 products in Class A,  273 products in Class B, and 679 products in Class C. Products that are not included in this classification are categorized as deadstock products. This research will focus only in Class A products. Through Forecasting, we can see which forecasting method is the best for each products. Through inventory management calculation, we can find that PT The Peak Connoisseurs can save by Rp 570,385,844.16.Keyword: Alcoholic Beverages, Wine, Deadstock, Inventory Management, Forecasting.